Novel splicing (c.6529-1G>T) and missense (c.1667G>A) mutations causing factor V deficiency. Issue 5 (July 2021) - Maharaj, Satish; Saenz Ayala, Sofia; Hu, Xiaolin; Chang, Simone; Sharma, Vivek; Majerus, Julie; Pruthi, Rajiv
Abstract : N/A: Congenital factor V deficiency (FVD) is a rare bleeding disorder. In this study, we investigated the genetic basis in an African American patient with factor V activity 3%. Custom sequence capture and targeted next-generation (NGS) sequencing of the F5 gene were undertaken followed by PCR and Sanger sequencing. Two novel variants were identified. In silico analyses correlated clinically with the patient's factor V activity and hemorrhagic tendency. A review of the literature regarding these genomic alterations is presented. We described two novel mutations causing moderate FVD. The first, Chr1:g.169483698C>A with cDNA change (F5):c.6529-1G>T, occurred in a conserved nucleotide at the canonical acceptor splice site of intron 24. The second, Chr1:g.169515775C>T with cDNA change (F5):c.1667G>A, was a missense variant of exon 11, affecting a highly conserved amino acid in the A2 domain. Further research into the mechanisms of F5 mutations leading to FVD and residual factor V expression are needed.